PENGARUH MEDIA PENDINGIN PADA PENGELASAN BAJA S45C MENGGUNAKAN METODE PENGELASAN GAS METAL ARC WELDING TERHADAP KEKERASAN DAN STRUKTUR MIKRO - Rachmadani Rachmadani; Suharno Suharno; Herman Saputro (Nozel : Jurnal Pendididikan Teknik Mesin, 2021)
This study aims to determine the effect of cooling media on microstructure and hardness values on alloy steel S45C using the welding method of Gas metal arc welding (GMAW). This research is using an experimental method. The data analysis technique used is descriptive comparative. The tool used for microstructure testing is Olympus Metallurgical Microscope and hardness test using the Vickers Hardness Tester. Based on the results of the study, it can be concluded that the results of the microstructure show an increase in the structure of pearlite after welding. In raw material, ferrite structures are seen evenly but in the welding results, GMAW which has cooled by using water, air, and oil cooling media show that ferrite is reduced in each specimen, so the pearlite structure dominates. The values of hardness and microstructure in the welding results using water, oil and aircooling media show differences in the level of hardness and microstructure. Specimens with water cooling media at the Heat Affected Zone (HAZ) test point have a higher hardness level of 315.4 VHN when compared to specimens using an oil cooling medium of 268.7 VHN and air conditioning media of 177.4 VHN. Specimens with water cooling media the microstructure in the Heat Affected Zone (HAZ) section showed more pearlite which was evenly distributed compared to specimens using other cooling media, or it could be concluded that the further away from the Las area and HAZ the smaller the pearlite content. This study shows that welding using variations in cooling media changes the microstructure and influences the hardness value of the S45C steel alloy